PENDAMPINGAN PROSES PEMBELAJARAN ILMU NAHWU SHARF DENGAN METODE ALMIFTAH LIL ULUM DI PONDOK PESANTREN DARUL MAGHFUR WONOSARI BONDOWOSO - Nurul Ma'rifah Nurul; Muhammad Husni (LPPM IAI Dar Aswaja Rokan Hilir, 2026)
The traditional Islamic educational institution known as the pondok pesantren plays an essential role in preserving classical scholarly traditions, particularly in the study of kitab kuning, which requires mastery of nahwu and sharaf. However, learning methods that remain centered on oral tradition often pose challenges for novice students in understanding Arabic texts. This Community Service Program (PKM) aims to enhance students’ understanding of nahwu and sharaf through the implementation of the Al-Miftah lil Ulum method at Pondok Pesantren Darul Maghfur Wonosari Bondowoso. This method was selected as a modern instructional innovation that presents Arabic grammatical principles in a simpler, more practical, and engaging manner, thereby bridging the gap between classical pesantren traditions and contemporary learning needs. The study employed an Empowerment-Based Research (EBR) approach grounded in a participatory-empowerment model, following the systematic stages of ECA–EVARED, which include exploration, planning and action, evaluation, and dissemination. The mentoring program was conducted through material delivery, practice exercises, observation, and assessment of students’ ability to read kitab kuning. The findings indicate that the Al-Miftah lil Ulum method effectively improved students’ skills in reading and understanding classical Islamic texts. Out of 48 participants, 23 students passed with good and fair categories. This success was supported by concise material presentation, attractive book design, and the use of nadzam and songs as memorization aids. Nevertheless, several challenges were identified, including student fatigue due to repeated material, limited instructional time, and the shortage of certified teachers. Overall, the Al-Miftah lil Ulum method proves effective in strengthening foundational nahwu and sharaf competencies, although further development is needed to achieve optimal outcomes.